A Comprehensive Analysis of 2013 Dystrophinopathies in China: A Report From National Rare Disease Center - Tong, Yuan-Ren; Geng, Chang; Guan, Yu-Zhou; Zhao, Yan-Huan; Ren, Hai-Tao; Yao, Feng-Xia; Ling, Chao; Wang, Dan-Chen; Chen, Lin; Cui, Li-Ying; Zhang, Shu-Yang; Dai, Yi (Frontiers in Neurology, 2020)
Introduction Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) are X-linked recessive neuromuscular disorders caused by mutations in the DMD gene. A high-quality database of DMD/BMD is essential not only for clinical practice but also for fundamental researches. We built the largest Chinese national dystrophinopathy database using the National Rare Diseases Registry System of China. Methods Peking Union Medical College Hospital (PUMCH) was the National Rare Diseases Center of China. This research involved 2014 patients with dystrophinopathies who were diagnosis-confirmed, registried and followed up at PUMCH from March 2011 to Decemeber 2018. Results Family history, clinical signs and treatment data were reported in DMD and BMD patients with different rates. All six serum biochemical indexes could distinguish DMD and BMD patients well. Copy number variations were the most frequent mutation type (79.2% in DMD and 84.3% in BMD), of which large deletions accounted for 88.4% and 88.6%, large duplications accounted for 11.6% and 11.4% in DMD and BMD respectively. An exon deletion hotspot located in exons 45-54 was observed in DMD and intron 44 was the most frequent deletion start point (26.5%). Duplication and single or oligo nucleotide variations seemed to distribute uniformly among all exons. Eleven patients were identified as ultra-rare mutation types . Other eleven patients suffered from two separate mutations simultaneously, some of which may take place via dependent mechanisms . Conclusions We established the largest hospital-based Chinese dystrophinopathy database via the National Rare Diseases Registry System. This study provides valuable information for further diagnostic and treatment studies of dystrophinopathy patients.